A new technique of impression making for an obturator in cleft lip and palate patient - Ravichandra K; Vijayaprasad K; Vasa A.A.K; Suzan S (Wolters Kluwer Medknow Publications, 2010)
Cleft lip and palate is a birth defect occurring in the orofacial region. One of the immediate problems to be addressed in a newborn with this defect would be to aid in suckling and swallowing. Here we present a case of a 5-day-old infant with unilateral cleft lip and palate for whom feeding obturator was made by using a simplified impression technique to facilitate feeding.